Reducing Treatment Burden for Age-Related Macular Degeneration Patients: A Systematic Review of Ranibizumab Port Delivery System - Paramitha, Dewa Ayu Anggi; Putri, Ajeng Kartika Ayu; Ardhia, Seruni Hanna; Jutamulia, Jovita (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesRanibizumab port delivery system (PDS) is a newly developed method that provides a continuous,long-term supply of ranibizumab into the vitreous, reducing the burden of monthly intravitrealinjection visits for neovascular age-related macular degeneration (nAMD) patients. This review aimsto evaluate the efficacy and safety of ranibizumab PDS in nAMD. MethodsAn extensive literature search was performed on 4 online databases: PubMed, Cochrane, ProQuest,and ScienceDirect. The inclusion criteria are human studies comparing ranibizumab port deliverysystem and intravitreal ranibizumab, English language, with full-text journal available. The mainoutcome measurements are best-corrected visual acuity (BCVA) in Early Treatment DiabeticRetinopathy Study (ETDRS) letters, central foveal thickness (CFT), and adverse events. ResultsTwo randomized controlled trials (RCTs) with a total of 638 adults were evaluated. At week 96,ranibizumab PDS reported observed mean BCVA changes from baseline (-1.0; +4.2; ETDRS letters)compared to monthly intravitreal ranibizumab (-1.1; +6.1; ETDRS letters). However, there was anincrease in mean CFT changes from baseline (+9.9; +22.3 vs ?1.3; ?35.8, ?m) and severe adverseevents frequency (22; 4 vs 4; 0) with ranibizumab PDS versus monthly intravitreal ranibizumab,respectively. ConclusionRanibizumab PDS showed comparable visual outcomes to intravitreal ranibizumab whiledemonstrating inferior anatomical outcomes and higher incidence of severe adverse effects. Despitethis, with fewer treatment visits required for up to 24 weeks, ranibizumab PDS can potentiallyreduce the treatment burden in nAMD patients with poor compliance. Further studies are needed toprovide better patient eligibility guidelines and recommendations for adverse event management ofranibizumab PDS.